Аналіз методів розпізнавання документів для автоматичної авторизації - Фурсов, А. Д. (ХНУРЕ, 2025)
This work focuses on the efficiency of document recognition for automatic authorization. The main emphasis is placed on the use of optical character recog-nition (OCR), neural network-based classification, and security verification algo-rithms. The study aims to identify key processing steps that help improve the ac-curacy and reliability of document-based authorization systems. The current con-text of the digital society highlights the importance of this research, as secure and efficient electronic identity verification remains a crucial task.
Keywords: розпізнавання документів; автоматична авторизація